Dirichlet Problem for Complex Poisson Equation in a Half Hexagon Domain. (10th February 2016) - Shupeyeva, Bibinur
Abstract : The parqueting-reflection method is applied to a nonregular domain and the harmonic Green function for the half hexagon is constructed. The related Dirichlet problem for the Poisson equation is solved explicitly.